2018
DOI: 10.1002/jrs.5533
|View full text |Cite
|
Sign up to set email alerts
|

ZO phonon of a buffer layer and Raman mapping of hydrogenated buffer on SiC(0001)

Abstract: We have measured spatial Raman maps of hydrogen intercalated quasi-free standing monolayer graphene (QFSMLG) on SiC(0001). We compare Raman spectra of QFSMLG with spectra of bare buffer layer, single-layer graphene, and bare SiC substrate. We also present the evolution of QFSMLG Raman spectra with the temperature and duration of hydrogen intercalation. We present new Raman modes, and, on the basis of polarization resolved measurements, we attribute them to the totally symmetric out-of-plane optical phonon (ZO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The characteristic distinction between the hydrogen intercalated and non-intercalated samples can be also found by the absence/presence of the peaks labeled (1), (2) and 3in inset of Figure 1. These peaks were attributed to the buffer layer [18,42]. The hydrogenated (QFMLG) and non-hydrogenated (SLG-vac, SLG-Ar) samples can be also distinguished by a low intensity background in the spectral range of the D peak.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic distinction between the hydrogen intercalated and non-intercalated samples can be also found by the absence/presence of the peaks labeled (1), (2) and 3in inset of Figure 1. These peaks were attributed to the buffer layer [18,42]. The hydrogenated (QFMLG) and non-hydrogenated (SLG-vac, SLG-Ar) samples can be also distinguished by a low intensity background in the spectral range of the D peak.…”
Section: Resultsmentioning
confidence: 99%
“…This sp 3 bonding was switched into sp 2 bonding by hydrogen intercalation [17,38]. More details on graphene growth and hydrogen intercalation can be found in our previous works [17,18,39].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Kruskopf et al [32] have observed similar peaks at about 1235 cm -1 and 1365 cm -1 and they attributed them to the vibrational density of states of the BL and the D-related peak, respectively, following Fromm et al [51]. Rejhon et al attributed the peak observed at 1237 cm -1 to "the LO/LA phonon branches at the Γ point" of the BL [41].…”
Section: Comparison Between Buffer Layer Under Graphene (C-bl1) and Nmentioning
confidence: 92%
“…These direct growth samples were synthesized at different growth temperatures ranging from 1600 to 1740°C (see table1 In the literature, a wide range of spectra have been reported for the BL from very disordered-like [28][29][30]39] to more ordered-like [20,31,34,40,41] as in the present work. Ordered-like BL can be viewed as a graphene layer sharing some sp 3 bonds with the substrate.…”
mentioning
confidence: 92%